2021
DOI: 10.3390/biomedicines10010087
|View full text |Cite
|
Sign up to set email alerts
|

Lipids and Lipoproteins in Health and Disease

Abstract: This Special Issue, “Lipids and Lipoproteins in Health and Disease: Focus on Targeting Atherosclerosis”, contains research articles and reviews devoted to the study of lipids in different processes, with a focus on the pathological changes that happen during atherosclerosis [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This favors the production of antiangiogenic factors into maternal circulation that contributes to endothelial damage. Previous study have shown that increased concentrations of antiangiogenic substances including soluble endoglin (sEng) and tyrosine kinase-1 (sFlt-1) 6 produced by the placenta into the mother's bloodstream during preeclampsia promote endothelial dysfunction and proteinuria 7 .…”
Section: Introductionmentioning
confidence: 99%
“…This favors the production of antiangiogenic factors into maternal circulation that contributes to endothelial damage. Previous study have shown that increased concentrations of antiangiogenic substances including soluble endoglin (sEng) and tyrosine kinase-1 (sFlt-1) 6 produced by the placenta into the mother's bloodstream during preeclampsia promote endothelial dysfunction and proteinuria 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Among the modifications of LDL which have been studied are oxidation [15], and desialylation [16]. HDL is involved in the transport of cholesterol from the arterial wall, playing an important role in regulating lipid levels with the low level of HDL that is connected with atherosclerosis development [17].…”
mentioning
confidence: 99%